Bilateral Blindness Due to Acute Isolated Sphenoid Sinusitis- Is It Reversible? A Case Report - Verma, Roshan Kumar; Panda, Naresh K (Journal of Medicine, 2014)
Acute isolated sphenoid sinusitis is a rare and is seen in only 3% of all cases of all sinusitis. It is frequently misdiagnosed because of its vague clinical presentation. We report a case of 35year old female who presented to our emergency department with complaints of painless rapidly developing bilateral vision loss. Non contrast computed tomography of paranasal sinuses showed only mild opacification of sphenoid sinus. Endoscopic sphenoidectomy was performed within 4 hrs of presentation. After 48 hrs of surgery the patient vision returned to 6/6 bilaterally. Acute sphenoid sinusitis should be considered in the differential diagnosis of acute vision loss. Awareness, early diagnosis, astute clinical sense and emergent intervention can prevent permanent complication. DOI: http://dx.doi.org/10.3329/jom.v15i2.20700 J MEDICINE 2014; 15 : 146-148